Environmental demogenetics of the potato late blight in Colombia (2024)
The potato late blight is known for its role in the Irish potato famine during the 19th century. This disease has been extensively studied ever since. However, despite being one of the most well-studied plant diseases in the world, it remains one of the biggest threats to global food security. The late blight is caused by the Oomycete Phytophthora infestans. In Colombia, due to the prevalence of this disease and the extended use of susceptible potato cultivars, the main control strategy against this disease is the continuous application of fungicides. This strategy has three main issues: first because of the toxicity of these compounds, it can negatively affect the health of growers and consumers, second repeated exposure of P. infestans to these fungicides leads to the development of resistance, and third its continuous use increases the costs of potato production. One way of reducing the use of fungicides without sacrificing the crop's safety is using epidemiological models of the late blight. These models project the proliferation of P. infestans in function of the environmental conditions. This allows the growers to only spray fungicides during the most favorable periods for the pathogen proliferation. These previous approaches are mechanistic and deterministic and do not consider the genetics of the pathogen. This work aimed to develop an integrative simulation model for the distribution of P. infestans in Colombia. The key novel idea of this model was to combine genetic, demographic, and environmental information in the simulation modeling and, therefore, in the predictions that could be obtained from it. This dissertation is divided into four chapters. The first chapter focuses on exploring the genetic landscape of P. infestans in Colombia. This chapter uses a novel machine learning-based tool to classify P. infestans microsatellite genotypes into their corresponding clonal lineage. In the second chapter, a new method to infer the rate of sexual reproduction of P. infestans was developed. Then, the integrative model for the distribution of P. infestans was developed in the third chapter. Genetic information gathered in the first two chapters and environmental and epidemiological information were used to build the proposed model. Finally, in the fourth chapter, the forecasting done by the model developed in the third chapter was used to produce easy-to-follow fungicide application schedules and recommendations that could be directly communicated to the growers through the miCampoApp application. This work then provides new tools for the analysis of genetic data from P. infestans and other polyploid organisms capable of both sexual and asexual reproduction. It also introduced a new modeling approach for the distribution of P. infestans and the appearance of the potato late blight in Colombia that can also be applicable in other regions with collected field data. Finally, this work proposes a way of directly communicating the model’s forecasting to the growers as part of a bigger agricultural cooperative structure.